2013
DOI: 10.4049/jimmunol.1301507
|View full text |Cite
|
Sign up to set email alerts
|

Defining CD8+ T Cell Determinants during Human Viral Infection in Populations of Asian Ethnicity

Abstract: The identification of virus-specific CD8+ T cell determinants is a fundamental requirement for our understanding of viral disease pathogenesis. T cell epitope mapping strategies increasingly rely on algorithms that predict the binding of peptides to MHC molecules. There is, however, little information on the reliability of predictive algorithms in the context of human populations, in particular, for those expressing HLA class I molecules for which there are limited experimental data available. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…This indicates that residues 266-275 are the minimal epitope of the N53 CD8 + T cell response. In previous study using bioinformatics NetMHCpan algorithm, the predicted minimal epitope for the N53 response was determined to be 9 amino acids at position 267-275 [25], which is within the 10-mer region identified in current study. Thus far, no other studies have reported the identification of the N53 CD8 + T cell epitope.…”
Section: Peptidementioning
confidence: 94%
“…This indicates that residues 266-275 are the minimal epitope of the N53 CD8 + T cell response. In previous study using bioinformatics NetMHCpan algorithm, the predicted minimal epitope for the N53 response was determined to be 9 amino acids at position 267-275 [25], which is within the 10-mer region identified in current study. Thus far, no other studies have reported the identification of the N53 CD8 + T cell epitope.…”
Section: Peptidementioning
confidence: 94%
“…A novel HLA-A*02:01 epitope of the SARS-CoV-1 N protein was further identified by Cheung et al [14]. Rivino et al [15] evaluated the reliability of predictive bioinformatic algorithms to identify CD8+ T cell epitopes in individuals of Asian origin infected with different viruses among whom were five patients with SARS-CoV-1. Although this study highlighted the limitations of such algorithms, the predictions were successful for peptides of SARS-CoV-1, as the predicted HLA restriction was concordant with the experimental HLA restriction for six out of seven N protein peptides (4 HLA-B*40:01, 1 HLA-B*55:02 and 1 HLA-B*15:25 restric-tions).…”
Section: Bioinformatic and Experimental Studiesmentioning
confidence: 99%
“…T‐cell epitopes have been identified using a variety of methods ranging from traditional epitope mapping strategies with 15‐mer peptide libraries overlapping by 10 amino acids spanning the entire viral proteome or selected proteins, to more modern approaches based on predictive algorithms that can determine immunogenic epitopes associated with chosen HLA molecules . Traditional methods are laborious but provide a comprehensive and unbiased identification of both CD4 + and CD8 + T‐cell epitopes, whereas predicative algorithms represent a high throughput technology but may not be accurate in terms of identifying immunodominant epitopes, particularly for less characterized HLA molecules expressed by Asian populations . Collectively, these studies show that dengue infection elicits a broad dengue‐specific T‐cell response that peaks around days 8–10 from fever onset and targets all viral proteins with a preferential recognition of the non‐structural proteins NS3, NS4b and NS5 .…”
Section: The ‘Long and Winding Road’ Of Denv T‐cell Epitope Discoverymentioning
confidence: 99%